Diabetes-Related Emergency Medical Service Activations in 23 States, United States 2015. (2nd November 2018) - Benoit, Stephen R.; Kahn, Henry S.; Geller, Andrew I.; Budnitz, Daniel S.; Mann, N. Clay; Dai, Mengtao; Gregg, Edward W.; Geiss, Linda S.
Abstract: Objective : The use of emergency medical services (EMS) for diabetes-related events is believed to be substantial but has not been quantified nationally despite the diverse acute complications associated with diabetes. We describe diabetes-related EMS activations in 2015 among people of all ages from 23 U.S. states.Methods : We used data from 23 states that reported ≥95% of their EMS activations to the U.S. National Emergency Medical Services Information System (NEMSIS) in 2015. A diabetes-related EMS activation was defined using coded EMS provider impressions of "diabetes symptoms" and coded complaints recorded by dispatch of "diabetic problem." We described activations by type of location, urbanicity, U.S. Census Division, season, and time of day; and patient-events by age category, race/ethnicity, disposition, and treatment with glucose. Crude and age-adjusted diabetes-related EMS patient-level event rates were calculated for adults ≥18 years of age with diagnosed diabetes using the Behavioral Risk Factor Surveillance System to estimate the population denominator.Results : Of 10, 324, 031 relevant EMS records, 241, 495 (2.3%) were diabetes-related activations, which involved over 235, 000 hours of service. Most activations occurred in urban or suburban environ- ments (86.4%), in the home setting (73.5%), and were slightly more frequent in the summer months. Most patients (72.6%) were ≥45 years of age and over one-half (55.4%) were transported to the emergency department. The overall age-adjusted diabetes-related EMS event rate was 33.9 per 1, 000 persons with diagnosed diabetes; rates were highest in patients 18–44 years of age, males, and non-Hispanic blacks and varied by U.S. Census Division.Conclusions : Diabetes results in a substantial burden on EMS resources. Collection of more detailed diabetes complication information in NEMSIS may help facilitate EMS resource planning and prevention strategies.